Daoist Reflections on the See-Saw of Contingency and Autonomy: The Laozi and Zhuangzi in Dialogue with Sandel, Rosa, Rorty, Gray - Paul Joseph D’Ambrosio (Religions, 2022)
Nearly all philosophical inquiry is rooted in contingency. From ontology and theories of God to politics and ethics, dealing with, explaining, planning for, or even following contingency is a consistent theme. In the background of their recent works, Michael Sandel, Hartmut Rosa, John Gray, and Richard Rorty all see contingency and autonomy in a see-saw relationship: more of one correspondingly results in less of the other. Daoist philosophical reflections provide a different take on contingency. We can still have an experience of “self” and of making choices without positing any notion of autonomy outside of contingency.